Biomass carbon quantum dot corrosion inhibitor as well as preparation method and application thereof

By using carbon quantum dot corrosion inhibitor prepared by biomass orange peel, the problems of poor stability and great toxicity of traditional corrosion inhibitors during the pickling process are solved, and efficient corrosion protection for aluminum alloys is achieved, and resource waste and environment are reduced. pollute.

CN119461341AInactive Publication Date: 2025-02-18LUDONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510031509.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional molecular corrosion inhibitors have problems such as poor stability, high toxicity and difficulty in degradation during the pickling process, which leads to excessive corrosion during the pickling process of metal products such as aluminum alloys, resulting in waste of resources and environmental pollution.

Method used

Biomass orange peel is used as the precursor to prepare biomass carbon quantum pit corrosion inhibitors (BCQDs) through a one-step hydrothermal method. This method has the characteristics of green and efficient, simple preparation, low cost and wide range of raw materials.

Benefits of technology

Effectively slows down the corrosion of aluminum alloy, realizes an efficient pickling process, reduces resource waste and environmental pollution, and the self-doping properties of the corrosion inhibitor enhance its adsorption effect on the metal surface and corrosion inhibition ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461341A_ABST
    Figure CN119461341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of corrosion inhibitors, and discloses a biomass carbon quantum dot corrosion inhibitor and a preparation method and application thereof.The preparation method of the biomass carbon quantum dot corrosion inhibitor comprises the steps that smashed orange peel powder is added into deionized water and stirred to be uniform; transferring the solution into a polytetrafluoroethylene reaction kettle, heating in a drying oven, cooling to room temperature after the reaction is finished, taking out the reaction kettle, filtering the solution by using a microporous filter membrane to remove unreacted substances, and purifying and dialyzing the solution by using a dialysis bag to obtain a yellowish-brown solution. And finally, pre-freezing the solution, freezing and drying in vacuum to obtain the final product BCQDs corrosion inhibitor. The biomass orange peel can be used as a carbon source, a nitrogen source, a sulfur source and a phosphorus source at the same time, and doping of various heteroatoms to the carbon quantum dots can be realized without adding other reagents. The prepared BCQDs corrosion inhibitor has the advantages of being environmentally friendly, efficient, easy to prepare, low in cost and wide in raw material source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion inhibitors, and in particular to a biomass carbon quantum dot corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] During the production and application process, metal products such as aluminum alloys are easily oxidized or covered with scale. Therefore, it is necessary to use inorganic acids such as hydrochloric acid and sulfuric acid for pickling to remove rust and dirt on the metal surface, thereby improving the cleanliness of the metal surface. However, excessive corrosion of metal materials often occurs during the pickling process, resulting in waste of metal resources, excessive production of pickling waste liquid, huge economic losses and environmental pollution. Therefore, the method of adding corrosion inhibitors to the pickling liquid system is often used to reduce the corrosion loss of the metal matrix and the excessive consumption of the pickling liquid during the pickling process. This method has the advantages of easy use, good effect and low cost. However, traditional molecular corrosion inhibitors are subject to many application restrictions during the pickling process due to their poor stability, high toxicity and difficulty in degradation. At present, with the implementation of the "dual carbon" goals and the growing demand for sustainable development, the development and research of efficient and green pickling corrosion inhibitors has become an important direction in the current field of corrosion inhibitor technology.

[0003] Carbon quantum dots (CQDs) are a new type of zero-dimensional carbon nanomaterial with a size of less than 10nm. They have good biocompatibility, fluorescence stability, water solubility, simple synthesis process, easy surface modification, and non-toxic or extremely weak toxicity. In recent years, they have been widely used in many fields such as battery storage, biosensing, bioimaging, photocatalysis, and biomedicine. The surface and edges of carbon quantum dots contain a large number of oxygen-containing functional groups such as hydroxyl and carboxyl, which can be used as active sites to produce adsorption on the metal surface. At the same time, the electronic properties and surface functional groups of carbon quantum dots can be regulated by doping them with heteroatoms such as nitrogen, sulfur, phosphorus, and fluorine to enhance their anchoring sites and thus enhance their adsorption and corrosion inhibition ability on the metal surface. Therefore, carbon quantum dots have the unique advantage of becoming a "green and efficient pickling corrosion inhibitor". At present, heteroatom doping modification of carbon quantum dots is usually achieved by adding compounds containing related elements, which will increase the difficulty and cost of the experiment. In addition, in the field of metal corrosion inhibition, there are few reports on carbon quantum dot corrosion inhibitors doped with nitrogen, sulfur, and phosphorus. Summary of the invention

[0004] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention aims to use renewable, biodegradable, non-toxic and harmless natural biomass orange peel as a precursor, which can be used as a carbon source, nitrogen source, sulfur source and phosphorus source at the same time, and adopt a simple one-step hydrothermal method to prepare a biomass carbon quantum dot corrosion inhibitor, which is applied to the corrosion protection of aluminum alloy in pickling solution. The corrosion inhibitor provided by the present invention has the characteristics of green and high efficiency, simple preparation, low cost and wide source of raw materials.

[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a method for preparing a biomass carbon quantum dot corrosion inhibitor, wherein the method for preparing the biomass carbon quantum dot corrosion inhibitor is: S1. Rinse the orange peel with deionized water, dry it at 120-125 °C for 2-3 h, and then crush it into powdery solid with a grinder and put it into a dryer for later use; S2, adding orange peel powder to deionized water and stirring evenly, then transferring the solution to a polytetrafluoroethylene reactor and heating it in an oven, and taking out the reactor after the reaction is completed and cooling to room temperature; S3, filtering the solution obtained in S2 using a microporous filter membrane to remove unreacted substances, and purifying the solution by dialyzing using a dialysis bag to obtain a yellow-brown solution; S4, transfer the solution obtained in S3 into a beaker, seal the open mouth of the beaker with a sealing film and place it in a refrigerator to freeze; S5. After piercing a number of holes on the sealing film on the beaker frozen in S4, vacuum drying is performed using a freeze dryer to obtain the final product, BCQDs corrosion inhibitor.

[0006] Preferably, the heating temperature in S2 is 180-185° C. and the heating time is 6-8 h.

[0007] Preferably, the microporous filtration membranes in S3 are 0.22 μm and 0.45 μm, and the molecular cutoff of the dialysis bag is 1000 Da.

[0008] Preferably, the freezing temperature in S4 is -25°C to -35°C, and the time is 10-15 hours.

[0009] Preferably, the freezing temperature in S5 is -50°C to -70°C, and the time is 36-48 hours.

[0010] Preferably, the application of the biomass carbon quantum dot corrosion inhibitor is: applying the BCQDs corrosion inhibitor to the surface corrosion protection of a metal substrate; including the application in a metal pickling solution; the metal substrate comprises any one of aluminum alloy, carbon steel and iron; the metal pickling solution comprises H 2 SO 4 , HCl, H3 PO 4 .

[0011] Preferably, at 25° C., in a 0.1 M HCl solution, when the BCQDs corrosion inhibitor addition amount is 150 mg / L, the corrosion inhibition efficiency at this time is measured by potentiodynamic polarization curve method to reach 92.16%.

[0012] Preferably, the biomass carbon quantum dot corrosion inhibitor is uniformly dispersed in morphology, with a particle size in the range of 1.21-5.96 nm and an average particle size of 3.34 nm.

[0013] Preferably, the biomass carbon quantum dot corrosion inhibitor has strong fluorescence properties, with a maximum excitation wavelength of 350 nm and a maximum emission peak at 439 nm.

[0014] 3. Beneficial technical effects (1) The raw material for preparing the corrosion inhibitor of the present invention is biomass orange peel, which is the redevelopment and utilization of orange peel and its application in corrosion protection of aluminum alloy, solving the problem of waste recycling and utilization, and has the advantages of being green and environmentally friendly and having a wide source of raw materials.

[0015] (2) The raw material (orange peel) of the present invention can be used as a carbon source as well as a nitrogen source, a sulfur source and a phosphorus source, thereby achieving self-doping of multiple heteroatoms without the need for an external heteroatom source.

[0016] (3) The present invention adopts a one-step hydrothermal synthesis method to prepare the BCQDs corrosion inhibitor, which has the advantages of simple operation and low cost.

[0017] (4) The present invention can effectively slow down the corrosion of aluminum alloy by adding a small amount of BCQDs corrosion inhibitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 , Schematic diagram of the preparation process of BCQDs corrosion inhibitor.

[0019] Figure 2 , Transmission electron microscopy image of the prepared BCQDs corrosion inhibitor.

[0020] Figure 3 , particle size distribution diagram of the prepared BCQDs corrosion inhibitor.

[0021] Figure 4 , XPS full spectrum of the prepared BCQDs corrosion inhibitor.

[0022] Figure 5 , UV-visible absorption spectrum of the prepared BCQDs corrosion inhibitor.

[0023] Figure 6, the fluorescence emission wavelength of the prepared BCQDs corrosion inhibitor under different excitation wavelengths.

[0024] Figure 7 , Nyquist plots of aluminum alloy in 0.1 M HCl solution without and with different concentrations of BCQDs corrosion inhibitor.

[0025] Figure 8 , potentiodynamic polarization curves of aluminum alloy in 0.1 M HCl solution without and with different concentrations of BCQDs corrosion inhibitor. DETAILED DESCRIPTION Example 1

[0026] A preparation step of BCQDs corrosion inhibitor ( Figure 1 ): S1. Rinse the orange peel with deionized water, dry it at 120 °C for 2 h, and then crush it into powdery solid using a grinder and put it into a dryer for later use; S2, add 4 g of orange peel powder to 70 ml of deionized water and stir evenly, then transfer the solution to a polytetrafluoroethylene reactor and heat it in an oven at 180 °C for 6 h. After the reaction is completed, cool to room temperature and take out the reactor; S3, filtering the solution obtained in S2 using 0.45 μm and 0.22 μm microporous filter membranes in turn to remove unreacted substances, and purifying the solution by dialyzing using a dialysis bag with a molecular cutoff of 1000 Da to obtain a yellow-brown solution; S4, transfer the solution obtained in S3 to a beaker, seal the open surface of the beaker with a sealing film and place it in a refrigerator to freeze at -30 °C for 12 h; S5. After piercing a number of holes in the sealing film on the beaker frozen in S4, use a freeze dryer to vacuum dry the mixture at a temperature of -60 °C for 48 h to obtain the final product, BCQDs corrosion inhibitor.

[0027] Transmission electron microscopy was used to characterize the structure of BCQDs corrosion inhibitor. Figure 2 As shown. Figure 2 It can be observed that the BCQDs corrosion inhibitor prepared by the present invention is spherical and evenly dispersed. The particle sizes of 210 BCQDs corrosion inhibitors were counted and their size distribution is as follows: Figure 3 As shown, the size of the obtained BCQDs is in the range of 1.21-5.96 nm, with an average particle size of 3.34 nm.

[0028] The elemental composition of BCQDs corrosion inhibitor was detected by XPS test. Figure 4From the full XPS spectrum, it can be seen that the BCQDs corrosion inhibitor mainly contains C, O, N, S, and P elements, which is attributed to the composition of orange peel. In addition to being a carbon source, it can also be used as a nitrogen source, a sulfur source, and a phosphorus source, achieving self-doping of multiple heteroatoms without the need for an external heteroatom source.

[0029] The optical properties of BCQDs were investigated using UV-visible spectrophotometer and fluorescence spectrophotometer. Figure 5 It can be seen that BCQDs have a characteristic absorption peak at 281 nm, which may be caused by the π-π* electronic transition of the C=C bond, and the broad absorption band around 355 nm can be attributed to the n-π* electronic transition of C=O. In addition, the fluorescence emission spectra under different excitation wavelengths are shown in Figure 2. Figure 6 As shown, with the gradual increase of the excitation wavelength, the fluorescence intensity first increases and then decreases. The maximum excitation wavelength is 350 nm, and the maximum emission peak is at 439 nm. Example 2

[0030] 30 mg, 100 mg and 150 mg of BCQDs corrosion inhibitor were added into 1L of HCl solution with a molar concentration of 0.1 M and stirred to dissolve. Then, electrochemical tests were carried out at room temperature to study the corrosion inhibition effect of BCQDs corrosion inhibitor on 7A04 aluminum alloy.

[0031] The size of the 7A04 aluminum alloy used in this experiment was 10 mm × 10 mm × 3 mm. During the electrochemical test, the 7A04 aluminum alloy working electrode was sealed with epoxy resin, and the exposed area was 1 cm 2 Before testing, the electrode was polished step by step with 600-3000 mesh SiC sandpaper, and then the electrode surface was cleaned with deionized water and ethanol, and finally dried with cold air for use.

[0032] Electrochemical tests were performed using a CHI660E electrochemical workstation. A three-electrode system was used, in which the reference electrode, auxiliary electrode, and working electrode were saturated calomel electrode, platinum electrode, and aluminum alloy electrode, respectively. The working electrode was placed in the corrosive medium and after the open circuit potential (OCP) was stabilized, the electrochemical impedance spectroscopy and potentiodynamic polarization curve were tested. The scanning frequency of the electrochemical impedance spectroscopy was 100 kHz to 10 mHz, and it was performed at the corresponding OCP with a sinusoidal AC wave amplitude of 5 mV. The scanning range of the potentiodynamic polarization curve test was -250 to +250 mVvs.OCP, and the scanning rate was 0.5 mV / s.

[0033] (1) Analysis of the corrosion inhibition effect of BCQDs on 7A04 aluminum alloy using electrochemical impedance spectroscopy At 25 °C, the Nyquist curves of 7A04 aluminum alloy in 0.1 M HCl solution containing different concentrations of BCQDs inhibitor are shown in Figure 2. Figure 7 As shown. The Nyquist curves of all samples are composed of a capacitive reactance arc in the high-frequency region and an inductive reactance arc in the low-frequency region. Compared with the samples in the blank solution without the addition of BCQDs corrosion inhibitor, the radius of the capacitive reactance arc of the sample increased significantly after the addition of BCQDs corrosion inhibitor, indicating that the addition of BCQDs corrosion inhibitor effectively inhibited the corrosion of 7A04 aluminum alloy. At the same time, it was found that with the increase of the concentration of BCQDs corrosion inhibitor, the radius of the capacitive reactance arc of the sample gradually increased, indicating that the corrosion inhibition effect gradually increased with the increase of the corrosion inhibitor concentration.

[0034] (2) Analysis of the corrosion inhibition effect of BCQDs corrosion inhibitor on 7A04 aluminum alloy using potentiodynamic polarization curve At 25 °C, the polarization curves of 7A04 aluminum alloy in 0.1 M HCl solution containing different concentrations of BCQDs inhibitor are shown in Figure 2. Figure 8 The main parameters obtained by fitting the polarization curve by Tafel extrapolation method are shown in Table 1, among which the corrosion inhibition efficiency η can be calculated by the following formula: In the formula, and Respectively represent the corrosion current density of 7A04 aluminum alloy samples in solutions without and with different concentrations of corrosion inhibitor.

[0035] Depend on Figure 8 It can be seen that compared with the samples in the blank solution, after adding different concentrations of BCQDs corrosion inhibitor, the corrosion current density of the sample anode and cathode both decreased, indicating that the BCQDs corrosion inhibitor has an inhibitory effect on both the anode reaction and the cathode reaction of the sample. From the data in Table 1, it can be seen that the corrosion potential of the sample after adding the corrosion inhibitor ( E corr ) compared with the blank solution sample E corr The negative shift was less than 85 mV, indicating that BCQDs corrosion inhibitor is a mixed corrosion inhibitor that mainly inhibits the cathode reaction. In addition, with the increase of BCQDs corrosion inhibitor concentration, the corrosion current density gradually decreased and the corrosion inhibition efficiency gradually increased. When the corrosion inhibitor concentration was 150 mg / L, the corrosion inhibition efficiency reached 92.16%.

[0036] Table 1: Polarization curve fitting parameters of 7A04 aluminum alloy in HCl solution containing different concentrations of BCQDs corrosion inhibitor.

[0037]

[0038] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a biomass carbon quantum dot corrosion inhibitor, characterized in that: The preparation method of the biomass carbon quantum dot corrosion inhibitor is: S1. Rinse the orange peel with deionized water, dry it at 120-125 °C for 2-3 h, and then crush it into powdery solid with a grinder and put it into a dryer for later use; S2, adding orange peel powder to deionized water and stirring evenly, then transferring the solution to a polytetrafluoroethylene reactor and heating it in an oven, and taking out the reactor after the reaction is completed and cooling to room temperature; S3, filtering the solution obtained in S2 using a microporous filter membrane to remove unreacted substances, and purifying the solution by dialyzing using a dialysis bag to obtain a yellow-brown solution; S4, transfer the solution obtained in S3 into a beaker, seal the open mouth of the beaker with a sealing film and place it in a refrigerator to freeze; S5. After piercing a number of holes on the sealing film on the beaker frozen in S4, vacuum drying is performed using a freeze dryer to obtain the final product, BCQDs corrosion inhibitor.

2. The method for preparing the biomass carbon quantum dot corrosion inhibitor according to claim 1, characterized in that: The heating temperature in S2 is 180-185° C. and the heating time is 6-8 h.

3. The method for preparing the biomass carbon quantum dot corrosion inhibitor according to claim 1, characterized in that: The microporous filtration membranes in the S3 are 0.22 μm and 0.45 μm, and the molecular cutoff of the dialysis bag is 1000 Da.

4. The method for preparing the biomass carbon quantum dot corrosion inhibitor according to claim 1, characterized in that: The freezing temperature in S4 is -25°C to -35°C, and the freezing time is 10-15 hours.

5. The method for preparing the biomass carbon quantum dot corrosion inhibitor according to claim 1, characterized in that: The freezing temperature in S5 is -50°C to -70°C, and the freezing time is 36-48 hours.

6. An application of a biomass carbon quantum dot corrosion inhibitor, characterized in that: The application of the biomass carbon quantum dot corrosion inhibitor is: applying the BCQDs corrosion inhibitor to the surface corrosion protection of metal substrates; Including application in metal pickling solution; the metal substrate includes any one of aluminum alloy, carbon steel and iron; the metal pickling solution includes H2SO4, HCl, H3PO4.

7. The use of the biomass carbon quantum dot corrosion inhibitor according to claim 6, characterized in that: In the 0.1 M HCl solution, the corrosion inhibition rate of 150 mg / L BCQDs corrosion inhibitor for 7A04 aluminum alloy is 92.16%.